Natural Occurrence of Ochratoxin ‘A’ in Raisins in Pakistan (Biological Sciences - PJSIR, 2006)
Grape raisins have become an important commodity in Pakistan. Ochratoxin ‘A’ and aflatoxin B1 are impor- tant mycotoxins from the human health point of view, which were determined in uncleaned grape raisins collected from local vendors during 1999-2002. A total of 160 samples of these raisins were analyzed for the quantitative detection of ochratoxin ‘A’ and aflatoxins. No aflatoxins were detected in any of the raisin samples above the detection limit of 1mg/Kg. Ochratoxin ‘A’ was determined using two different methods. Method–I involved methanol-aqueous extraction of the raw unclean raisins, followed by the adjustment of the extract to pH 2 with 2 N hydrochloric acid, and partitioned into chloroform. Method-II involved methanol-equeous extraction, followed by cleanup with the clarify- ing agent, ammonium sulfate, and partitioned into chloroform. The minimum amount of ochratoxin ‘A’ detected in the samples, with method-I, was 3.2 + 0.9 mg/Kg, while with method-II the minimum value noted was 9.7 + 0.8 mg/Kg. The maximum amount determined in the samples analysed using method-I was 16.8+ 2.7 mg/Kg, while with method-II the maximum value was 29.2 + 2.9mg/Kg